Optimalisasi Zakat Infak dan Sedekah Melalui Badan Amil Zakat Nasional Kabupaten Magelang - Effendi, Hamron; Putro, Widodo (Journal of Indonesian Rural and Regional Government, 2025)
This study analyzed the optimization of zakat, infaq, and sadaqah (ZIS) at the Magelang Regency National Zakat Management Body (BAZNAS Kab. Magelang), focusing on BAZNAS's strategies and the role of the Magelang Regency Government in maximizing ZIS collection from government officials, BUMD employees, village heads, and village officials. The study also examined the management and distribution of ZIS by BAZNAS Kab. Magelang for poverty alleviation in the Magelang Regency. The research is descriptive and qualitative, utilizing primary and secondary data from BAZNAS Kab. Magelang. The findings indicated that: 1. the Magelang Regency Government's role in ZIS optimization through Bupati Instruction Number 3 of 2024 was influential. 2. BAZNAS Kab. Magelang's efforts in maximizing ZIS collection included ZIS education and establishing Zakat This research aims to analyze the optimization of zakat, infaq, and sedekah (ZIS) from civil servants (ASN), employees of Regional Public Service Agencies (BUMD), village heads, and village officials at the National Amil Zakat Agency (BAZNAS) of Magelang Regency, as well as to investigate the management and distribution of ZIS for poverty alleviation in Magelang Regency. The research is descriptive and qualitative, utilizing primary and secondary data from BAZNAS Kab. Magelang. The findings indicated that: 1. the Magelang Regency Government's role in ZIS optimization through Bupati Instruction Number 3 of 2024 was influential. 2. BAZNAS Kab. Magelang's efforts in maximizing ZIS collection included ZIS education and establishing Zakat Collection Units in regional government organizations and mosques. 3. Furthermore, ZIS were distributed for poverty alleviation within Magelang Regency. The study aims to provide insights for the Magelang Regency Government and BAZNAS Kab. Magelang to further optimize ZIS collection and utilization for poverty reduction.